2014
DOI: 10.1371/journal.pone.0089440
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Spatiotemporal Trends of Dengue Transmission in the Asia-Pacific Region, 1955–2004

Abstract: BackgroundDengue fever (DF) is one of the most important emerging arboviral human diseases. Globally, DF incidence has increased by 30-fold over the last fifty years, and the geographic range of the virus and its vectors has expanded. The disease is now endemic in more than 120 countries in tropical and subtropical parts of the world. This study examines the spatiotemporal trends of DF transmission in the Asia-Pacific region over a 50-year period, and identified the disease’s cluster areas.Methodology and Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…Another possible mechanism which could explain a higher morbidity in HbSC disease is neo-angiogenesis. It has been reported that neo-angiogenesis and retinopathy are more frequent in HbSC patients ( Banu et al, 2013 ). It is possible that blood vessels produced by neo-angiogenesis are more permeable in response to inflammatory cytokines such as High mobility group box 1 (HMGB1) protein which increases vascular permeability of endothelial cells in a dose dependent manner in in-vitro experiments ( Ong et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism which could explain a higher morbidity in HbSC disease is neo-angiogenesis. It has been reported that neo-angiogenesis and retinopathy are more frequent in HbSC patients ( Banu et al, 2013 ). It is possible that blood vessels produced by neo-angiogenesis are more permeable in response to inflammatory cytokines such as High mobility group box 1 (HMGB1) protein which increases vascular permeability of endothelial cells in a dose dependent manner in in-vitro experiments ( Ong et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion of red blood cells which tested DENV seronegative but were RNA positive with high viral load (N10 7 copies/mL) can lead to DENV infections in transfusion recipients [67]. Several countries and regions with a high prevalence of DENV have investigated DENV among blood donors and recipients to evaluate its impact on blood safety, as well as to develop a proper donor enrollment strategy to reduce the transfusion-transmission risk [68][69][70].…”
Section: Dengue Viruses (Denv)mentioning
confidence: 99%
“…About 50-100 million people suffer from DF every year with approximately 22,000 deaths per year. The prevalence of DF has increased about 30 folds in the last 50 years and 40% of people are at risk of DF [2][3]. One of the effective diagnosis procedures for DF includes the non-structural protein 1 (NS1) antigen test with a sensitivity of 48.5%-58.6% and specificity of 92.5%-99.4%.…”
Section: Introductionmentioning
confidence: 99%